Vicinal difunctionalization of alkenes by four-component radical cascade reaction of xanthogenates, alkenes, CO, and sulfonyl oxime ethers - Sumino, Shuhei; Fukuyama, Takahide; Sasano, Mika; Ryu, Ilhyong; Jacquet, Antoine; Robert, Frédéric; Landais, Yannick (Beilstein Journal of Organic Chemistry, 2019)
Four-component coupling reactions between xanthogenates, alkenes, CO, and sulfonyl oxime ethers were studied. In the presence of hexabutylditin, working as a propagating radical reagent, the chain reaction proceeds, as expected, taking into account reagents polarities, affording the corresponding functionalized α-keto oximes. Although yields are modest, this rare one-pot four-component process is easy to carry out and the resulting compounds, bearing multiple functionalities, have the potential for further elaboration.
Keywords: CO; multicomponent reaction; radicals; sulfonyl oxime ethers; xanthogenates